2017
DOI: 10.1016/j.ajog.2016.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Patient, surgeon, and hospital disparities associated with benign hysterectomy approach and perioperative complications

Abstract: BACKGROUND Hysterectomy is among the most common major surgical procedures performed in women. Approximately 450,000 hysterectomy procedures are performed each year in the United States for benign indications. However, little is known regarding contemporary US hysterectomy trends for women with benign disease with respect to operative technique and perioperative complications, and the association between these 2 factors with patient, surgeon, and hospital characteristics. OBJECTIVE We sought to describe cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
85
1
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 27 publications
6
85
1
5
Order By: Relevance
“…Prior investigation into complications from hysterectomy by Mehta, et al, identified that Black race was associated with higher rate of complications. 21 This same analysis identified that minimally invasive hysterectomy was also associated with lower complications, however, the study did not investigate if minimally invasive hysterectomy mitigated complication rates specifically for women of black race. The findings from our analysis help to bridge this gap in knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Prior investigation into complications from hysterectomy by Mehta, et al, identified that Black race was associated with higher rate of complications. 21 This same analysis identified that minimally invasive hysterectomy was also associated with lower complications, however, the study did not investigate if minimally invasive hysterectomy mitigated complication rates specifically for women of black race. The findings from our analysis help to bridge this gap in knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…7Y11 Several publications have shown the benefits of robotic surgery over open surgery in the general population, including reduced operative blood loss, lower incidence of intraoperative and postoperative complications, and shorter hospital stays along with comparable recurrence rates and survival. 7,12Y20 Despite some data showing that elderly women have similar outcomes to their younger counterparts, 21 there are discrepancies in the treatments offered to these 2 groups, probably due to experience, tradition, and access to a robotic surgical system. The less aggressive approach to surgery in elderly women with endometrial cancers may be based on a perception that elderly patients have a lower tolerance of extensive surgical interventions.…”
mentioning
confidence: 99%
“…10 A high-volume patient concentration is known to benefit patient outcomes in other areas of complex oncological urology, 11 14 and has been demonstrated to have outcome benefits in benign surgery in other disciplines. 15,16 Although there often seems to be resistance to the process of centralisation, 9 it appears that its acceptability to patients, particularly as far as the need to travel for both outpatient evaluation and inpatient care is concerned, is outweighed by the perceived clinical benefit. 17 19 Therefore, the distance between tertiary or quartenary centres is not a major factor that inhibits the adoption of regional or supra-regional network structures.…”
Section: Discussionmentioning
confidence: 99%